ChemInform Abstract: Metal Free Quick Introduction of Azole in to Azine Nucleus: Acid Catalyzed Reissert—Henze Reaction. Issue 17 (28th April 2014) - Velavan, A.; Mondal, Dibyendu; Survase, Sachin
Abstract Optimum reaction conditions are examined for the reaction of N‐tosylimidazoles derivatives (II) or (X) with pyridine, quinoline or isoquinoline N‐oxides to give the corresponding imidazole‐substituted N‐heterocycles.